Computational analysis of transmission loss in an exhaust muffler / Mohd A 'zmi Yunus, Ahmad Azlan Mat Isa and Mohamed Dahalan Mohamed Ramli (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2008)
Mufflers are commonly used for automobile exhaust system to attenuate the noise levels produced by automobile engine to the atmosphere. Since the muffler becomes an important part in automobile exhaust system a restrictive environmental legislation requires silencer designers to use high performance and reliable techniques as such that any improvement on the exhaust muffler will contribute a significant impact on the quality of the automobile exhaust system. In order to overcome these problems a basic design muffler with computational analysis of the acoustics characteristics for absorption and simple expansion muffler was carried out. The transmission loss of such mufflers is determined using Transfer Matrix Method (TMM). Modification design variables available through simulation for acoustics characteristics are realised. The efficiency of the proposed technique is illustrated by comparing the results with those available in established literature. The results shows good agreement with other methods, thus demonstrating the validity and the reliability of the method.